Chemical Compositions of Hydrocolloids Produced from Nutlets of Salvias - Rike Yudianti; Lucia Indrarti; Myrtha Karina; Masahiro Sakamoto; Jun-ichi Azuma (Masyarakat Peneliti Kayu Indonesia, 2007)
Hydrocolloids of three species of Salvias (S. miltiorrhiza, S. sclarea and S. viridis) was analyzed their chemical compositions after isolation of hydrocolloids from seed coats. Isolation was conducted after expanding out completely in water. Hydrocolloids produced from S. miltiorrhiza, S. sclarea and S. viridis have cellulose contents about 18.6%, 25.3% and 35.4% and hemicelluloses contents about 80%, 73.4% and 62%, respectively. Native hydrocolloids produced from S. sclarea and S. viridis were rich in glucose about 48.6% and 55.4%, respectively, while the other one, S. miltiorrhiza, was rich in xylose, about 85.1%. Distribution of these polysaccharides in S. miltiorrhiza, S. sclarea and S. viridis were 86.5%, 71.0% and 63.2% (acidic polysaccharides) and 13.8%, 29.0% and 36.5% (neutral polysaccharide), respectively. Acidic polysaccharides of hydrocolloids produced from three species of Salvias contain high amount of xylose (88.8 91.9%). Neutral sugar compositions in neutral polysaccharides of hydrocolloids produced from three species of Salvias, however, were rich in glucose (25.7 37.5%) and galactose (31.3 60.4%), the ratio being changed depending on species. Acidic sugar in the acidic polysaccharides from three Salvia spp. was identified as glucuronic acid by High Performance Anion Exchange Chromatography (HPAEC). Glucuronic acid contents in the acidic fractions of S. miltiorrhiza, S. sclarea, S. viridis were estimated about 25%, 22% and 27%, respectively. These results elucidate that hydrocolloids have amorphous structure containing branch glucuronic acid in acidic polysaccharides structure. The present of glucuronic acid is predicted attach to xylan.